Chronic Ossified Epidural Hematoma After Ventriculoperitoneal Shunt Insertion: A Case Report - Seyithanoglu, Hakan; SEYİTHANOĞLU, MEHMET HAKAN; Guzey, Feyza Karagoz; Emel, Erhan; Ozkan, Nezih; Aycan, Abdurrahman (My University, 2010)
Chronic calcified/ossified epidural hematoma is an uncommon complication of ventricular shunt surgery. There are only 4 cases related to valve-regulated shunt operations in the literature. It may be seen especially in young patients with chronic hydrocephalus, probably due to craniocerebral disproportion. The precise mechanism of the calcification or ossification of the hematoma is not known, however, the dura mater seems to play a part in this process. A 17-year-old girl with triventricular hydrocephalus was treated with a ventriculoperitoneal shunt system including a medium pressure flow control valve. She was admitted with a complaint of severe headache after three years and a bifrontal calcified/ossified epidural hematoma was seen. The calcifying hematoma was removed and the patient-s headache resolved. Although the use of high or medium pressure valves, valves with an antisiphon device, adjustable pressure valves or flow control valves have been recommended to prevent this complication in previous reports, it was seen that our case had been treated with a medium pressure flow control valve.
Keywords: Case Report